02 Portici Advanced Design Studio - Bernieri, Adriana; Coppolino, Francesca (ADS Advanced Design Studio, 2021)
The design work carried out on the city of ​​Portici represented, for the students in the last year of the Master's Program in Architecture 5UE, an important experiment, from a design and professional point of view, towards the development of an approach aimed at finding an adequate and factual response to the multiple needs posed by the reality of the context in which it operates. The book collects the results of the work carried out during the 2019-2020 academic year, highlighting the multiplicity of aspects and design topics addressed, as well as the variety of the proposed solutions. The structure of the book reflects this experimental approach, starting with the exploration of some preliminary topics and methods, examined in the "Essays" section; continuing through the study of the "collaborative mapping" and the interaction with the environment and with the people who live in these places; finally, working on assembling and defining a "synthesis" of data and investigations through the design proposals, described in the "Projects" section. To try to solve the existing critical issues, yet to enhance the potential and the various heritage of the city of Portici, the project proposals were built grafting into the existing, not oriented towards the definition of a closed form and a predetermined function. On the contrary, it has implied to work on the idea of an open form, which reuses and recycles what already exists, including multiple possibilities of use and continuously changing its perimeter, extending and incorporating urban pieces of different nature. Scenarios of new possible meanings and new urban transformations are, therefore, the result of this work, made up of different levels of study and research related to the overall idea of ​​Portici as a "City-Park".